(untitled) (Comillas Journal of International Relations, 2020)
This article analyses two key contents of Global Citizenship Education in the educational regulations of Compulsory Secondary Education in the Autonomous Community of Castilla and León: inequalities and peaceful conflict resolution. Documentary analysis is used as a methodology, since it is the analysis of legislative texts. The results show that these dimensions are dealt with in the legislation, but in a very superficial way, only in three subjects and without global issues acquiring an important presence. It is concluded that the legislation of Castilla and Leon presents deficiencies when it comes to forming citizens who acquire a global perspective of the problems existing in other parts of the world and their causes.